Impersonal Verbal Constructions in Biblical Hebrew Active, Stative, and Passive - Notarius, Tania 1967- (2021)
In this paper I focus on the syntactic properties of subjects in impersonal verbal constructions in Biblical Hebrew. It is claimed that four types of subjectless verbal clauses—active finite and participial plural, active finite singular, passive, and stative—feature three types of impersonal subject: covert indefinite pronoun, inflectional morpheme, and zero-subject. It will be demonstrated that these subjects have different, only partly overlapping syntactic properties: The covert indefinite pronoun implies an animate subject that does not necessitate "collective interpretation" and can have generic scope; the subject can be topicalised, negated, and relativised, the verbal predicate is temporally vague. The 3rd masculine plural inflectional morpheme implies an animate collective subject; it can be controlled from the matrix clause and be used for participant tracking and anaphora; the verbal predicate is quite precisely anchored in time. The dummy zero-subject has no explicit subject properties; it can be theorised that the syntactic slot of a subject is taken by an overt cognate argument (Cause or Theme) of stative or passive verbs, but practically such a subject leaves no syntactic traces.
Keywords: Biblical Hebrew; impersonal clause; Passive; stative; Subject; Syntax